Measurement of pollution of water and sediment of the Al-Hammar Marsh for some heavy elements - Eynas R Gdawa; Kamil K. Fahad (University of Thi-Qar Journal of agricultural research, 2024)
The study was conducted to determine the monthly changes that occur in environmental factors and pollution levels occurring in the water and sediments of the Al-Hammar marsh in Dhi-Qar Governorate. Samples were collected from the Al-Hammar marsh from November 2023 AD to April 2024 AD. The current study included measuring some physical and chemical characteristics, air temperature and... Water, turbidity, pH, electrical conductivity, dissolved oxygen, and estimation of the concentrations of the heavy elements cadmium (Cu), copper (Cu), and zinc (Zn) in the water and sediments of the Hammar marsh. It turned out that the concentrations of the heavy elements follow the following order: Copper < zinc < cadmium, their concentrations in sediments and bioaccumulation in them follow the following order: zinc < copper < cadmium. The results showed that the Al-Hammar marsh water was suitable for human consumption, but the sediment levels were high